The effects of simulated acid rain of different pH-levels on biomass and leaf area in Sunflower (Helianthus annuus) - Lal, Nand; Singh, Hemlata (Current Botany, 2013)
The effects of simulated acid rain (SAR) of different pH [distilled water-7.0 (control), 5.7, 4.5 and 3.0] were studied using sunflower (Helianthus annuus) cv. ‘Morden’ as test system. Sunflower plants were sprayed with 30 ml acid rain solution at weekly intervals starting from two leaved stage till initiation of flowering in the early morning under natural environment. Evaluation of SAR effects on plant roots, shoots and leaves at peak growth and maturity stages revealed that biomass and lengths of the studies plant parts decreased with decreasing pH of acid rain solution. Comparison of biomass and length at peak growth and maturity stages recorded maximum difference in control the difference narrowed with increasing acidity. The differences at acidic treatments were well-marked with leaves followed by roots and shoots, respectively. In case of length, roots and shoots were more adversely affected as compared to leaves. Acid rain application caused reduction in leaf area which has direct bearing on growth of roots and shoots, and overall plant growth. Effects of SAR on sunflower increased more dramatically with the increase of SAR acidity and were correlated with exposure times and doses of SAR. The study indicates the sunflower plant to be an acid rain sensitive system and demands for breeding acid rain tolerant varieties in view of growing industrialization and expanding acid rain geographical areas.